Penggunaan Eksperimen Sederhana dalam Pembelajaran IPA di Sekolah Dasar: Tinjauan Pustaka - Syahrial, Syahrial; Juneda, Juneda; Dinda Saskia; Devi Margaretha (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This literature study is to analyze the use of simple experimental methods when learning natural science (IPA) in elementary schools (SDS) and assess its impact on students' interest and understanding. Elementary education plays an important role as a foundation for learning, and requires appropriate methods to improve students' concepts. Science experiments provide hands-on learning opportunities that can deepen your understanding of scientific concepts. The literary research method is used to analyze various related literature for the use of simple experiments in elementary school science learning. The results of the analysis show that simple experiments have a positive impact on students' understanding of scientific concepts, active participation, critical thinking, providing practical learning experiences, and increasing interest in learning. However, its implementation faces challenges such as limited institutions and willingness to teach. Although this study has obstacles, simple experiments continue to be effective in improving the quality of science learning in elementary schools, and these findings provide insights for teachers and political decision makers in designing more effective science learning.